A nanocompartment system contributes to defense against oxidative stress in Mycobacterium tuberculosis - Katie A Lien (eLife Sciences Publications Ltd, 2021)
Encapsulin nanocompartments are an emerging class of prokaryotic protein-based organelle consisting of an encapsulin protein shell that encloses a protein cargo. Genes encoding nanocompartments are widespread in bacteria and archaea, and recent works have characterized the biochemical function of several cargo enzymes. However, the importance of these organelles to host physiology is poorly understood. Here, we report that the human pathogen Mycobacterium tuberculosis (Mtb) produces a nanocompartment that contains the dye-decolorizing peroxidase DyP. We show that this nanocompartment is important for the ability of Mtb to resist oxidative stress in low pH environments, including during infection of host cells and upon treatment with a clinically relevant antibiotic. Our findings are the first to implicate a nanocompartment in bacterial pathogenesis and reveal a new mechanism that Mtb uses to combat oxidative stress.